Analysis Of Students Understanding of Tiktok Applications - Roza, Gytha Silvia; Islamiah, Fitriatul; Sa’diyah, Halimah Nur; Lestari, Mira (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This study aims to find out how the influence of the TikTok application learning on students' understanding at MTs Negeri 4 Tanjung Jabung Timur in fiqh subjects. The type of research used in this study is descriptive qualitative by describing in detail the understanding of students' learning about the Tiktok application. The population used in this study amounted to 30 students, while the sample used in this study amounted to using a purposive sampling technique. Data was taken using observation and questionnaire methods. So it can be seen that there is an influence of the TikTok application on the fiqh learning process by 73.3% of student scores increasing, 23.3% of student scores not changing, and 3.3% of student scores decreasing.